Relationship between Decreased Serum Superoxide Dismutase Activity and Metabolic Syndrome: Synergistic Mediating Role of Insulin Resistance and β-Cell Dysfunction - Li, Wei; Xu, Lingling; Li, Yu-xiu; Ping, Fan; Zeng, Jingbo; He, Shuli; Ma, Chunxiao; Li, Pingping; Lv, Lu; Ma, Chifa; Liu, Yiwen; Zhang, Huabing (Oxidative medicine and cellular longevity, 2020)
The interplays of cellular aging and oxidative stress (OS) markers form a complex network, which has been reported to be interrelated with numerous age-related and metabolic diseases, including metabolic syndrome (MS). However, given the multifactorial mechanisms of MS, several important confounders such as dietary factors and the reciprocal effect among these markers have not been considered and adjusted in previous investigations regarding the associations of cellular aging and OS markers with MS and its related metabolic abnormalities. To explicate this, we conducted a cross-sectional study among 533 Chinese adults. All the participants underwent a 75 g oral glucose tolerance test. Dietary data were collected via a 24-hour dietary recall and subsequently analyzed by a registered dietitian using nutrition calculation software. Clinical diagnosis of MS was made according to the revised National Cholesterol Education Program Adult Treatment Panel III criteria (2004) with waist circumference cutoff modified for an Asian population. The leukocyte telomere length, mitochondrial DNA copy number, 8-hydroxy-2-deoxyguanosine, superoxide dismutase (SOD) activity, and glutathione reductase were examined. SOD activity was significantly decreased in MS subjects (62.06±16.89 U/mL vs. 56.25±22.61 U/mL, P=0.001) and exhibited a descending trend across sequential increase of MS component number (P for trend=0.031). SOD activity is modestly correlated with glucose indicators and insulin sensitivity and β-cell function indices and was independently and negatively correlated with the level of triglyceride. An independent association between SOD activity and MS was observed after adjusting for metabolic indicators, dietary factors, cellular aging, and OS markers, as well as insulin sensitivity and β-cell function indices. However, the statistical significance of the association between SOD activity and MS was attenuated after adjusting for the Matsuda insulin sensitivity index (ISIM) and insulin secretion-sensitivity index-2 (ISSI-2), suggesting a possible mediating effect. Therefore, we conducted a mediation model analysis, which showed that decreased ISIM and ISSI-2 partially and synergistically mediated the contribution of decreased SOD activity to MS. In conclusion, decreased SOD activity is an independent predictor for increased risk of MS, and insulin resistance and β-cell dysfunction partially mediate the relationship between decreased SOD activity and MS.